MR1-dependence of unmetabolized folic acid side-effects - Tang, Jeffry S.; Cait, Alissa; White, Reuben M.; Arabshahi, Homayon J.; O’Sullivan, David; Gasser, Olivier (Frontiers in Immunology, 2022)
The fortification of flour with folic acid for the prevention of neural tube defects (NTD) is currently mandated in over eighty countries worldwide, hence compelling its consumption by the greater part of the world’s population. Notwithstanding its beneficial impact on rates of NTD, pervasive folic acid supplementation has invariably led to additive daily intakes reaching well beyond their original target, resulting in the circulation of unmetabolized folic acid. Associated idiopathic side-effects have been described, ranging from allergies to cancer. Herein, we hypothesize that their elusive etiology is linked to the immunosuppressive folic acid metabolite 6-formylpterin, which interferes with the still emerging and varied functions of Major Histocompatibility Complex-related molecule 1 (MR1)-restricted T cells. Accordingly, we predict that fortification-related adverse health outcomes can be eliminated by substituting folic acid with the bioequivalent folate vitamer 5-methyltetrahydrofolate, which does not break down into 6-formylpterin.